PENUGASAN TUTOR DI LABORATORIUM SEJARAH SEBAGAI PENGUAT KREATIVITAS MAHASISWA - Murdi, Lalu; Saputra, Bambang Eka (Universitas Hamzanwadi, 2019)
This study aims to analyze the importance of media in the history of learning that not only uses digital in accordance with current developments with era 4.0, but also how a teacher is able to bridge the past by presenting artifacts, relics, images, even miniatures of the past for easier understood. The existence of a laboratory or museum in this case can be a direct bridge to connect what they have learned with their empirical reality in the past. This research uses a qualitative approach with a phenomenological method with several methods of data collection ranging from interviews, observations, document studies and documentation. The results showed that students involved as totor who were assigned to explain each period with some media available at the Hamzanwadi University history education laboratory showed many developments starting from the ability to understand the historical context at a certain period and their ability to explain to the public or students who normally visit the laboratory. One interesting approach that Hamzanwadi University's history education program has tried to develop in recent years is to make students as tutors to explain to students who visit the history education laboratory. Students who are assigned are randomized every semester in turn, so that each of them truly understands each historical object as assigned.